Comparative Study of Learning Methods in Character Education Management Among Islamic Religious Education Teachers and Christian Religious Education Teachers - Witoro, Johanes (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This research aims to analyze the comparison between Islamic and Christian education management in terms of character education. The type of research that will be used quasi experiment with the design of a paired control group (matching pretest-posttest control group design). The results showed that character education in students at STT Biblika Jakarta has adequate intellectual knowledge as a scholar who meets the needs of the community, in the fields of Biblical, Theological, Spiritual Service, and Work in society. In addition, they have the character of a leader of good character and become an example as a clergyman. Do love in his life and imitate Christ. Able to answer people's problems and and live presents peace and love each other. Be a leader with high integrity towards the responsibilities he gives. Able to live socially and bring renewal or innovation in society. Meanwhile, student character education at UIN Maliki Malang, with character education model developed, namely making the figure of ulul albab as the foundation. In developing the character of students, UIN Maliki Malang bases on the historical values of the establishment of Islamic University and Vision, Mission of the college. The theoretical foundation used as a handle in developing character education based on ulul albab is the conception of Islamic teachings and the foundation of educational ilosois. The purpose of character education based on Ulul Albab UIN Maliki Malang is to form a Muslim person who has the values of ulul albab.